Assistance For Students to Improving Islamic Religious And Economic Education In Islamic Boarding Schools in Indonesia - Katni Katni; Dato' Ab Halim Tamuri; Adib Khusnul Rois; Femi Astika Candra Chairani; Syamsul Arifin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
The Ahmad Dahlan Qur'an Memorization Islamic Boarding School in Ponorogo Regency is an Islamic boarding school under the auspices of the Muhammadiyah organization, which has a different level of academic quality compared to modern boarding school students, including the following: 1) Mastery of the yellow books or classical Islamic literature in Arabic across various religious disciplines. 2) In- depth knowledge of Arabic grammar or Nahwu, Sharaf, balaghah (meaning, bayan, badi’), and logic, as these subjects are studied seriously and occupy a significant portion of the modern boarding school curriculum. 3) Proficiency in memorizing the Qur'an. 4). Entrepreneurship program for students. Students are required to study Islam comprehensively to develop a religious character. The pesantren emphasizes values such as discipline, a sense of responsibility, independence, simplicity, and honesty. In addition, they are also taught about entrepreneurship. It is hoped that the students will develop a character that can master their faith and possess the skills for independence after graduating from the pesantren.